“No Viral, No Justice”: Unveiling the Phenomenon of Digital Vigilantism from a Psychological Perspective - Angela, Lisa; Aulia, Wina; Rahma, Balya Galuh Jiehan Safira (Faculty of Psychology Universitas Gadjah Mada, 2024)
The rapid advancement of the cyber world has spurred new behaviors and a complex transition from real-life to online behaviors. One behavior arising from this development is digital vigilantism. This concept utilizes social media and the internet to punish or publicly shame those perceived as normatively guilty. Using a narrative literature review method, this article aimed to explore digital vigilantism behavior and analyze it through the lens of psychology. The literature review examined seven research articles discussing digital vigilantism published from 2014-2024. Key focuses include the concept of digital vigilantism, analysis based on psychology theories (such as social identity theory and theory of justice), as well as an examination of its strengths and weaknesses. The article provides fresh insights into digital vigilantism and its intersection with psychology.